Endovascular therapy of arteriovenous fistulae with electrolytically detachable coils - Jansen, Olav; Dörfler, Arnd; Forsting, Michael; Hartmann, Marius; Kummer, Rüdiger von; Tronnier, Volker; Sartor, Klaus (Neuroradiology, 1999)
We report our experience in using Guglielmi electrolytically detachable coils (GDC) alone or in combination with other materials in the treatment of intracranial or cervical high-flow fistulae. We treated 14 patients with arteriovenous fistulae on brain-supplying vessels - three involving the external carotid or the vertebral artery, five the cavernous sinus and six the dural sinuses - by endovascular occlusion using electrolytically detachable platinum coils. The fistula was caused by trauma in six cases. In one case Ehlers-Danlos syndrome was the underlying disease, and in the remaining seven cases no aetiology could be found. Fistulae of the external carotid and vertebral arteries and caroticocavernous fistulae were reached via the transarterial route, while in all dural fistulae a combined transarterial-transvenous approach was chosen. All fistulae were treated using electrolytically detachable coils. While small fistulae could be occluded with electrolytically detachable coils alone, large fistulae were treated by using coils to build a stable basket for other types of coil or balloons. In 11 of the 14 patients, endovascular treatment resulted in complete occlusion of the fistula; in the remaining three occlusion was subtotal. Symptoms and signs were completely abolished by this treatment in 12 patients and reduced in 2. On clinical and neuroradiological follow-up (mean 16 months) no reappearance of symptoms was recorded.